Donor extracellular vesicle trafficking via the pleural space represents a novel pathway for allorecognition after lung transplantation. Issue 7 (26th March 2022) - Habertheuer, Andreas; Chatterjee, Shampa; Sada Japp, Alberto; Ram, Chirag; Korutla, Laxminarayana; Ochiya, Takahiro; Li, Wenjun; Terada, Yuriko; Takahashi, Tsuyoshi; Nava, Ruben G.; Puri, Varun; Kreisel, Daniel; et al.
Abstract : Restoration of lymphatic drainage across the bronchial anastomosis after lung transplantation requires several weeks. As donor antigen and antigen presenting cell trafficking via lymphatics into graft‐draining lymph nodes is an important component of the alloresponse, alternative pathways must exist that account for rapid rejection after pulmonary transplantation. Here, we describe a novel allorecognition pathway mediated through donor extracellular vesicle (EV) trafficking to mediastinal lymph nodes via the pleural space. Pleural fluid collected early after lung transplantation in rats and humans contains donor‐specific EVs. In a fully MHC mismatched rat model of lung transplantation, we demonstrate EVs carrying donor antigen preferentially accumulate in mediastinal lymph nodes and colocalize with MHC II expressing cells within 4 h of engraftment. Injection of allogeneic EVs into pleural space of syngeneic lung transplant recipients confirmed their selective trafficking to mediastinal lymph nodes and resulted in activation of T cells in mediastinal, but not peripheral lymph nodes. Thus, we have uncovered an alternative pathway of donor antigen trafficking where pulmonary EVs released into the pleural space traffic to locoregional lymph nodes via pleural lymphatics. This pathway obviates the need for restoration of lymphatics across the bronchial anastomosis for trafficking of donor antigen to draining lymph nodes. Abstract : Following lung transplantation, donor‐specific extracellular vesicles traffic to locoregional mediastinal lymph nodes via the pleural space where they co‐localize with MHC‐II expressing cells and promote T cell responses via the semi‐direct or indirect pathway, obviating the need for intact afferent lymphatics for donor antigen trafficking across the bronchial anastomosis.